Paul Cézanne e lo statuto della pittura (Itinera, 2021)
On the basis of a remark made by Giorgio Morandi on his own journey in the world of art, the essay aims to clarify the revolutionary significance of the method that underlies the plastic representation in Paul Cézanne and the contribution it has provided to the definition of the statute of painting in the twentieth century (color field painting). The analysis of the interpretations of Cézanne’s work by David Herbert Lawrence, Rainer Maria Rilke and Peter Handke thus has the merit of showing the nature of the need for truth that guided Cézanne in the choice of oil or watercolour as material capable from time to time of explaining the fundamental difference that exists between the movement with which a being discloses itself into the wide open and its presence as a fact here at hand.
Keywords: Paul Cézanne, Giorgio Morandi, painting, watercolour, color field painting